A Model and Empirical Test of Evolving Consumer Perceived Brand Innovativeness and its two-way Relationship with Consumer Perceived Product Innovativeness. Issue 4 (November 2020) - Shams, Rahil; Brown, Mark; Alpert, Frank
This paper examines the evolution of consumer perceived brand innovativeness through its relationship with product innovativeness. A survey of 617 respondents measured consumer perceptions, brand attitude, and purchase intention, with data analysed using structural equation modelling. Results indicate that after exposure to a product innovation, consumers' existing perception of brand innovativeness and perception of the technological newness of the innovation shape their perception of product innovativeness. This leads to an updating of perceptions of innovativeness at the brand level, which subsequently influence both brand attitude and purchase intention outcomes. It also mediates the impact of product innovativeness on these variables. This model of the evolution of brand innovativeness shows how it can be strengthened (or weakened) by product innovativeness. A key managerial implication is that investment and production of highly innovative products will result in a virtuous cycle of increasing future perceptions of product and brand innovativeness.